Biomimetic Total Synthesis of 6a,7,8,9,10,10a-Hexahydro-3,6,9-trimethyl-6-(4-methylpent-3-en-1-yl)-1,9-epoxy-6H-dibenzo-[b,d]pyran and Its Diastereoisomer - Zeng, Huiying; Duan, Daiping; Tang, Boxiao (Synlett, 2015)
The first total synthesis of 6a,7,8,9,10,10a-hexahydro-3,6,9-trimethyl-6-(4-methylpent-3-en-1-yl)-1,9-epoxy-6H-dibenzo[b,d]pyran and its diastereoisomer via tandem pericyclic reactions were achieved in one step. Our biomimetic strategy features a sequential Aldol-type addition, 6π electrocyclization, and hetero-Diels–Alder cycloaddition, where three rings, two C–C bonds, and two C–O bonds were spontaneously constructed in a highly efficient way.
Keywords: biomimetic; total synthesis; tandem pericyclic reactions; 6π electrocyclization; hetero-Diels–Alder cycloaddition